Performance of Anaerobic Membrane Bioreactors (AnMBRs) with Different Dosages of Powdered Activated Carbon (PAC) at Mesophilic Regime in Membrane Fouling Control - Chong, Connie Tung (2015)
Anaerobic membrane bioreactor (AnMBRs) has been widely employed in the municipal and industrial wastewater treatment due to its attractive advantages. By the comparison to the conventional aerobic membrane bioreactor, AnMBR has low yield anaerobic microbes which produce relatively lower sludge concentration, requires minimum energy that can produce biogas to be used as energy source. In this study, it was found that higher dosages of powdered activated carbon (PAC) had better membrane fouling control. To investigate the mechanisms involved in helping the fouling control, (i) particle size distribution; (ii) concentration of mixed liquor suspended solids (MLSS) and mixed liquor volatile suspended solids (MLVSS); (iii) chemical oxygen demand (COD); (iv) extracellular polymeric substances (EPS) concentration analysis as well as (v) biogas production were measured and analysed to support and explain the findings.